APPEARANCE OF THE MOURNING GECKO, Lepidodactylus lugubris (DUMÉRIL & BIBRON, 1836), IN THE CAGE OF ORIENTAL WHITE-EYE (Zosterops palpebrosus) - Rury Eprilurahman (Scripta Biologica, 2019)
The nocturnal parthenogenetic species, mourning gecko (Lepidodactylus lugubris), has been recorded in Sleman, Daerah Istimewa Yogyakarta, Java, Indonesia. There has yet no specific information of its distribution in Java and its behaviour. One out of three individues observed was successfully caught. A single specimen collected from The Oriental white-eye (Zosterops palpebrosus) cage is reviewed along with literature reports of the occurrence of the species. It is likely that population of this invasive gecko has been established in the region.